Chondroitin Sulphate-Chitosan Based Nanogels Loaded with Naringenin-β-Cyclodextrin Complex as Potential Tool for the Treatment of Diabetic Retinopathy: A Formulation Study - Zucca G; Vigani B; Valentino C; Ruggeri M; Marchesi N; Pascale A; Giovilli G; Malavasi L; Sandri G; Rossi S (International Journal of Nanomedicine)
Gaia Zucca,1 Barbara Vigani,1 Caterina Valentino,1 Marco Ruggeri,1 Nicoletta Marchesi,1 Alessia Pascale,1 Giulia Giovilli,2 Lorenzo Malavasi,2 Giuseppina Sandri,1 Silvia Rossi1 1Department of Drug Sciences, University of Pavia, Pavia, 27100, Italy; 2Department of Chemistry and INSTM, University of Pavia, Pavia, 27100, ItalyCorrespondence: Silvia Rossi; Barbara Vigani, Department of Drug Sciences, University of Pavia, Via Taramelli 12, Pavia, 27100, Italy, Email silvia.rossi@unipv.it; barbara.vigani@unipv.itPurpose: The main purpose of the study was the formulation development of nanogels (NHs) composed of chondroitin sulfate (CS) and low molecular weight chitosan (lCH), loaded with a naringenin-β-cyclodextrin complex (NAR/β-CD), as a potential treatment for early-stage diabetic retinopathy.Methods: Different formulations of NHs were prepared by varying polymer concentration, lCH ratio, and pH and, then, characterized for particle size, zeta potential, particle concentration (particles/mL) and morphology. Cytotoxicity and internalization were assessed in vitro using Human Umbilical Vein Endothelial Cells (HUVEC). The NAR/β-CD complex was prepared and evaluated for morphology, complexation efficiency, and solubility. Finally, the most promising NH prototype was loaded with NAR/β-CD (NH@NAR/β-CD) and further characterized for encapsulation efficiency, loading capacity, opacity and cytotoxicity on HUVEC; in vitro release test and DPPH assay were performed to investigate NH capability to sustain NAR release and NH@NAR/β-CD antioxidant properties, respectively.Results: NH properties were influenced by polymer concentration, lCH ratio, and pH. N3 (0.5 mg/mL; lCH=1.5:1; pH = 5) and N9 (0.5 mg/mL; lCH=1:1; pH = 5) showed optimal characteristics, including small size (< 350 nm) and positive zeta potential, facilitating cellular uptake. The NAR/β-CD complex showed 71% complexation efficiency and enhanced NAR solubility. Since characterized by superior properties and better in vitro biocompatibility, N3 was loaded with NAR/β-CD. N3@NAR/β-CD capability to sustain in vitro NAR release, radical scavenging activity and in vitro biocompatibility were finally demonstrated.Conclusion: The physico-chemical properties of N3@NAR/β-CD were responsible for their cell uptake, suggesting their potential to target retinal endothelial cells. The high NAR/β-CD complexation efficiency and the sustained NAR release over 72 hours could guarantee the maintenance of an effective drug concentration at the damage site while reducing the injection number. Further studies about the safety and the effectiveness of the intravitreal injection of NHs@NAR/β-CD will be performed on a diabetic animal model. Keywords: polyelectrolyte complexation, cellular uptake, inclusion complex, antioxidant properties, intravitreal administration